Expert Witness against the Crime of Medical Malpractice in Indonesia - Mohd Zamre Mohd Zahir; Muhammad Hatta; Khairunnisa, Cut; Yati Nurhayati (Cendekia : Jurnal Hukum, Sosial dan Humaniora, 2024)
In the legal aspect, the position and role of the doctor as an expert witness is very important. Their expert testimony even plays major consideration in the decision of the judges. However, it is not easy to invite doctors as expert witnesses if the suspects are their colleagues. In addition, the doctor, the expert witness, would give less objective testimony in court to protect their colleagues. Also, it is very rare that expert witness points out different medical measures carried out by the suspects. Proof mechanism by using a doctor as an expert witness is a flaw in law enforcement in cases of medical malpractice. Globally, there are some countries such as the Netherlands, Belgium, France and Switzerland that have introduced reversed burden proof systems.